Delightful landscapes: Elements of the Greco-Roman Tradition in the Work of the Post-Byzantine Painter Ioannis Permeniatis - Charchare, Eleni (Actual Problems of Theory and History of Art, 2015)
The paper examines the influence of the Graeco-Roman tradition on the work of Ioannis Permeniatis, a post-Byzantine painter who worked in Venice, where he was an active member of the Greek Confraternity in 1523. In his paintings features of the Byzantine tradition are combined with elements adopted from Western art, especially in terms of landscape settings. Some elements in particular, such as shepherds and sheep, castles and rustic buildings, leafy trees and atmospheric distances, are typical of the pastoral landscape, which was popular in the Venetian painting of the first decades of the 16th century. The emergence of pastoral painting in Venice was stimulated by the revival of the pastoral poetry of Сlassical antiquity. Furthermore, classical texts promoted the Renaissance appreciation of the countryside and landscape painting. Ioannis Permeniatis followed popular Venetian models and created his distinctive “delightful landscapes”, thus linking post-Byzantine painting with Renaissance art and classical tradition.
Keywords: Ioannis Permeniatis; post-Byzantine painting; Greek Confraternity of Venice; Renaissance Venetian art; Graeco-Roman tradition; landscape painting; pastoral landscape